Role of gamification in classroom teaching: Pre-service teachers’ view - Rita Wong Mee Mee; Tengku Shahrom Tengku Shahdan; Md Rosli Ismail; Khatipah Abd Ghani; Lim Seong Pek; Wong Yee Von; Adelaide Woo; Yugeshineey Subba Rao (International Journal of Evaluation and Research in Education (IJERE), 2020)
Planning a creative learning environment is not an easy task. Teachers prefer to teach traditionally in chalk-and-talk approach during language teaching. However, this does not fit learners of the 21st Century as they prefer game-like activities instead of pen-and-paper lessons. Hence, the introduction of gamification in classroom would result in immediate enthusiasm and curiosity, which leads to the learners’ willingness to learn. Gamification prepares learners to be active and take responsibility upon their own learning. Lessons filled with fun games are believed to be more effective in producing a positive outcome as learners are motivated to play more although they do not realise the fact that they are learning subconsciously. This study aimed to explore views of 33 pre-service teachers in using gamification in language teaching during their 16-week internship at local primary schools around Selangor, Malaysia. A quantitative survey research method was used by administering a set of questionnaires at the end of their internship. The data collected was then analysed and presented in the form of tables. The results showed that integrating gamification into language learning improved learners’ creative, critical and problem-solving skills. Thus, interesting and engaging activities spark learners’ interest in language learning subconsciously.